Postulat Periode Akuntansi: Konsep, Implementasi, dan Implikasi pada Laporan Keuangan: Penelitian - Naufal Fauzan Siregar; Fendi Irwan Gulo; Tabitha Marisi Uli Aritonang; Hizkia Agustina Simaremare; Jufri Darma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The accounting period postulate is a foundational principle that divides an entity’s economic life into artificial intervals, thereby ensuring that financial statements are systematic and comparable. This study investigates the conceptual framework, practical implementation, and implications of the accounting period postulate on financial reporting quality. A qualitative-descriptive methodology was adopted, employing a comprehensive literature review and content analysis of scholarly articles, accounting standards (PSAK, IASB), and regulatory guidelines. Key findings indicate that temporal segmentation enhances the timeliness, relevance, and comparability of financial information but necessitates precise period-end accrual adjustments and introduces the risk of earnings management. Moreover, the postulate underpins essential accounting principles such as the matching concept and going-concern assumption—and holds strong normative authority in standard-setting. However, its consistent application remains limited among small and medium-sized entities. The study concludes that strengthening educational initiatives, reinforcing internal controls, and refining regulatory standards are imperative to uphold the integrity and reliability of periodic financial reporting.